2020
DOI: 10.1186/s12891-020-3044-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and radiographic predictors of acute compartment syndrome in the treatment of tibial shaft fractures: a retrospective cohort study

Abstract: Background: The purpose of this study was to evaluate the association between epidemiological, clinical and radiographic factors of patients with tibial shaft fractures and the occurrence of acute compartment syndrome. Methods: 270 consecutive adult patients sustaining 273 tibial shaft fractures between January 2005 and December 2009 were included in this retrospective cohort study. The outcome measure was acute compartment syndrome. Patient-related (age, sex), fracture-related (high-vs. low-energy injury, iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 29 publications
2
33
0
Order By: Relevance
“…There were not enough ACS cases (four) among distal intra-articular fractures to draw conclusions (Table 3). The ACS occurrence rates found in this study fall within previously reported rates in the literature, which ranged from 0.7-12% for tibial plateau fractures (even as high as 53% for some higher-energy subgroups) [8][9][10][11][12][13][14][15][16], from 3-11.5% for tibial shaft fractures [8,12,13,[17][18][19], and from 2-12.5% for pilon tibial fractures [8,13,20]. For this reason, it can be assumed that the study cohort closely represents the habitual spectrum of tibia fractures, and that its results might be generalized to most tibia fracture patients.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…There were not enough ACS cases (four) among distal intra-articular fractures to draw conclusions (Table 3). The ACS occurrence rates found in this study fall within previously reported rates in the literature, which ranged from 0.7-12% for tibial plateau fractures (even as high as 53% for some higher-energy subgroups) [8][9][10][11][12][13][14][15][16], from 3-11.5% for tibial shaft fractures [8,12,13,[17][18][19], and from 2-12.5% for pilon tibial fractures [8,13,20]. For this reason, it can be assumed that the study cohort closely represents the habitual spectrum of tibia fractures, and that its results might be generalized to most tibia fracture patients.…”
Section: Resultssupporting
confidence: 86%
“…Indeed, our results showed that distal extra-articular fracture might be a protecting factor against ACS occurrence, when compared to a more proximal location. This nding might be explained by the fact that the distal tibia is surrounded by a less bulkier muscle mass, and that the energy released during trauma is transmitted into tendinous soft tissues rather than muscle, thus less likely leading to the potential development of ACS [19].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations